A High Conductivity 1D π–d Conjugated Metal–Organic Framework with Efficient Polysulfide Trapping‐Diffusion‐Catalysis in Lithium–Sulfur Batteries. Issue 10 (28th January 2022) - Yang, Dawei; Liang, Zhifu; Tang, Pengyi; Zhang, Chaoqi; Tang, Mingxue; Li, Qizhen; Biendicho, Jordi Jacas; Li, Junshan; Heggen, Marc; Dunin‐Borkowski, Rafal E.; Xu, Ming; Llorca, Jordi; et al.
Abstract: The shuttling behavior and sluggish conversion kinetics of the intermediate lithium polysulfides (LiPS) represent the main obstructions to the practical application of lithium–sulfur batteries (LSBs). Herein, a 1D π–d conjugated metal–organic framework (MOF), Ni‐MOF‐1D, is presented as an efficient sulfur host to overcome these limitations. Experimental results and density functional theory calculations demonstrate that Ni‐MOF‐1D is characterized by a remarkable binding strength for trapping soluble LiPS species. Ni‐MOF‐1D also acts as an effective catalyst for S reduction during the discharge process and Li2 S oxidation during the charging process. In addition, the delocalization of electrons in the π–d system of Ni‐MOF‐1D provides a superior electrical conductivity to improve electron transfer. Thus, cathodes based on Ni‐MOF‐1D enable LSBs with excellent performance, for example, impressive cycling stability with over 82% capacity retention over 1000 cycles at 3 C, superior rate performance of 575 mAh g −1 at 8 C, and a high areal capacity of 6.63 mAh cm −2 under raised sulfur loading of 6.7 mg cm −2 . The strategies and advantages here demonstrated can be extended to a broader range of π–d conjugated MOFs materials, which the authors believe have a high potential as sulfur hosts in LSBs. Abstract : Rationally designed multifunctional polysulfide mediators based on a novel 1D π–d conjugated Ni‐based metal–organic framework (MOF) (Ni‐MOF‐1D) are demonstrated as excellent cathode materials in lithium–sulfur batteries, realizing the adsorption‐catalysis‐conversion of polysulfides, and thus batteries with exceptional lifespan are delivered.